Novel three-dimensional tin/carbon hybrid core/shell architecture with large amount of solid cross-linked micro/nanochannels for lithium ion battery application. (15th March 2015) - Yang, Zunxian; Meng, Qing; Yan, Wenhuan; Lv, Jun; Guo, Zaiping; Yu, Xuebin; Chen, Zhixin; Guo, Tailiang; Zeng, Rong
Abstract: Uniform Sn/C hybrid core/shell nanocomposites were synthesized by a combination of electrospinning and subsequent thermal treatment in a reducing atmosphere. The particular three-dimensional architecture, consisting of a Sn@C nanoparticle core and porous hollow carbon nanofiber shell, is characterized by many micro/nanochannels, enhanced mechanical support from the three-dimensional hollow carbon shell, and the abundant porous carbon matrix. The as-prepared Sn/C core/shell nanomaterials exhibit excellent electrochemical performance. They display a reversible capacity of 546.7 mAhg −1 up to 100 cycles at the current density of 40 mAg −1 and good rate capability of 181.8 mAhg −1 at 4000 mAg −1 . These results indicate that the composite could be a promising anode candidate for lithium ion batteries. Highlights: Sn/C core/shell composites were synthesized by an electrospinning, a hydrothermal process, and further thermal treatment. The best-performing 3D composite consists of a Sn@C nanoparticle core and porous hollow carbon nanofiber shell. The Sn/C composite electrode exhibit excellent Li ion storage capacity and cycling stability.